Understanding Digital Transformation Initiatives: Case Studies Analysis - Furjan Martina Tomičić; Tomičić-Pupek Katarina; Pihir Igor (Business Systems Research, 2020)
Background: Complexity of the digital transformation (Digital Transformation) paradigm and its relation to the fourth technological revolution face companies with serious challenges when it comes to keeping up with the competition or becoming a leader in operating industries.